2016
DOI: 10.1002/2016gl070107
|View full text |Cite
|
Sign up to set email alerts
|

Seismogenic stress field estimation in the Calabrian Arc region (south Italy) from a Bayesian approach

Abstract: A new high‐quality waveform inversion focal mechanism database of the Calabrian Arc region has been compiled by integrating 292 mechanisms selected from literature and catalogs with 146 newly computed solutions. The new database has then been used for computation of posterior density distributions of stress tensor components by a Bayesian method never applied in south Italy before the present study. The application of this method to the enhanced database has allowed us to provide a detailed picture of seismote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 65 publications
5
21
0
Order By: Relevance
“…CC BY 4.0 License. than elsewhere in the region (see, among others,Totaro et al, 2016). The stress inversion results 269 obtained in the present study are reported inTable 1and Fig.…”
supporting
confidence: 60%
“…CC BY 4.0 License. than elsewhere in the region (see, among others,Totaro et al, 2016). The stress inversion results 269 obtained in the present study are reported inTable 1and Fig.…”
supporting
confidence: 60%
“…They also consider the “Pollino fault” inactive, except in the vicinity of the intersection with the Castrovillari fault. The few available focal mechanisms in this area indicate E‐W extension by N‐S striking faults and are inconsistent with NW striking faults (Totaro et al, ).…”
Section: The Youngest Exposed Apenninic Thrust Faultmentioning
confidence: 93%
“…Published GPS measurements and deformation models of the forearc D'Agostino et al, 2011;Kreemer et al, 2014) exhibit rather low strain rates (~10-20 nanostrain/yr). The combination of slow trenchward motion with the lack of thrust faulting mechanisms in the instrumental record (Neri et al, 2009;Presti et al, 2013;Totaro et al, 2016) led some researchers to hypothesize that the Calabrian subduction is no longer active (Monaco et al, 1996;Perouse et al, 2012). Yet different clusters of earthquakes above m = 6 are reported for onshore Calabria (Rovida et al, 2016;Tiberti et al, 2017), that is, for the portion of the forearc lying approximately above the subduction megathrust, in open contrast with the low observed geodetic strain rates.…”
Section: 1002/2017gl076554mentioning
confidence: 99%
“…(a) Seismicity and GPS data. Focal mechanisms for earthquakes of magnitude >2.6 (fromTotaro et al, 2016) are shown in the dashed red polygon (southern Calabria). Outside this area we plot earthquakes with m ≥ 4.5.…”
mentioning
confidence: 99%